Socioeconomic inequality in financial hardship in accessing quality healthcare services in Ethiopia: a community-based cross-sectional study - Tsega, Yawkal; Birhan, Zelalem; Adamu, Kidist (Frontiers in Public Health, 2025)
BackgroundThe 2030 Agenda for Sustainable Development aims to ensure that no one is left behind in health. However, the high magnitude of catastrophic health expenditure (CHE) and impoverishing health expenditure (IHE) remain global challenges. The financial hardship caused by healthcare has not been extensively studied in Ethiopia to date. Therefore, this study aimed to assess socioeconomic inequality in financial hardship and its determinants among households in the South Wollo zone, Ethiopia.MethodsThis cross-sectional study surveyed 845 households in the South Wollo zone from 1 May to 31 May 2023. Financial hardship was measured using the IHE and CHE metrics. The households were considered to experience IHE if their health expenditure pushed them below a poverty line of $2.15 (ETB 118.25) and considered to experience CHE if their health expenditure exceeded 10% of their total expenditure. Costs were estimated using prevalence-based and patient-perspective approaches. STATA version 17.0 was used for data management and analysis. We used the cixr and lorenz estimate STATA commands to estimate the concentration index (CIX) and generate the concentration curve (CC), respectively. An adjusted odds ratio (AORs) with a 95% confidence interval and a p-value of <0.05 were used to determine statistical significance.ResultsThe CIX for wealth status was −0.17 (CI: −0.23, −0.11), with a p-value <0.001, indicating significant socioeconomic inequality in financial hardship of healthcare. The incidence of CHE was ~30% (95%CI; 26.91–33.16%) at the 10% threshold, while the incidence of IHE was ~4% at the $2.15 poverty line. Significant determinants of CHE included the poorest wealth status (AOR: 4.80, CI: 2.61–8.86), older age of the household head (AOR: 3.40, CI: 1.52–7.60), lack of insurance (AOR: 2.70, CI: 1.67–4.38), chronic illnesses (AOR: 5.12, CI: 3.24–8.10), being widowed (AOR: 4.30, CI: 1.27–14.57) or divorced (AOR: 6.45, CI: 1.89–21.10) in terms of marital status of the household head, and seeking traditional healthcare (AOR: 2.47, CI: 1.60–3.81).ConclusionThis study revealed that there was significant inequality in financial hardship of health expenditure across household wealth categories. The incidences of CHE and IHE were higher. The wealth status of the household, insurance status, marital status of the household head, chronic illness, and seeking traditional healthcare were the key determinant factors of CHE. Therefore, policymakers should focus on underprivileged households to ensure effective healthcare financial risk protection (FRP).